2022
DOI: 10.1177/17085381221111010
|View full text |Cite
|
Sign up to set email alerts
|

Acute left iliofemoral vein thrombosis: Comparison between simple and bony May-Thurner syndrome in CT venography

Abstract: Objectives To explore the etiology of May-Thurner syndrome (MTS) with acute iliofemoral deep vein thrombosis (DVT) regarding imaging findings and clinical features. Methods We retrospectively analyzed 57 patients with acute left iliofemoral DVT from 2015 to 2020. The diameter of left common iliac vein (LCIV) at the maximal compression site and its percent compression regarding the average diameter of the uncompressed iliac vein were recorded in central and distal portions of the LCIV according to the location … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 33 publications
(64 reference statements)
0
1
0
Order By: Relevance
“…23,24 Recent studies have proven that CT venography (CTV) is efficient for evaluating venous anatomic abnormalities including stenosis or thrombosis. 25 Although, contrast, cost, and availability are major considerations of CTV, this examination has advantages in selected patients. In particular, we observed that 70.3% of patients with IVC thrombosis suffered from obvious back pain in this study.…”
Section: Discussionmentioning
confidence: 99%
“…23,24 Recent studies have proven that CT venography (CTV) is efficient for evaluating venous anatomic abnormalities including stenosis or thrombosis. 25 Although, contrast, cost, and availability are major considerations of CTV, this examination has advantages in selected patients. In particular, we observed that 70.3% of patients with IVC thrombosis suffered from obvious back pain in this study.…”
Section: Discussionmentioning
confidence: 99%